Influence of the Strategic Planning System on the Pace of Socio-Economic Development of the Russian Federation's Constituent Entities - S. N. Miroshnikov (Управленческое консультирование, 2021)
A double whammy of coronavirus and the resulting economic stagnation cause the risk of stimulating policy of the survival and failure of strategic planning. At the same time, it is in an era of change that we must first adhere to a stable system of values and pre-defined goals and plans. This will allow you not only to stay on the right course, not to go astray, but also to work ahead of the situation. The paper presents the results of a comparative  assessment of the rate of change in quantitative indicators that characterize the state of regional socioeconomic  systems in 2009, 2014 and 2018, depending on the use of strategic planning in the subjects of the Russian Federation.